Relationship between nocturnal blood pressure dip and β-parapapillary atrophy zone choroidal vessel density in normal-tension glaucoma patients - Jimin Park; Woo Keun Song; Min Su Baek; Jooyoung Yoon; Anna Lee; Ko Eun Kim; Michael S. Kook (PLoS ONE, 2025)
Purpose To investigate the relationship between nocturnal blood pressure (BP) dip and parapapillary choroidal vessel density (pCVD) in patients with normal-tension glaucoma (NTG) Methods This study analyzed 267 eyes of 267 untreated NTG patients who underwent 24-hour (h) intraocular pressure (IOP) and ambulatory BP monitoring in the habitual position. Patients were classified into 3 groups [non-dippers (nocturnal BP dip < 10%), dippers (nocturnal BP dip between 10% and 20%, and over-dippers (nocturnal BP dip > 20%)], and pCVDs were measured by using optical coherence tomography angiography (OCTA) images. Logistic regression analyses were performed to identify clinical factors associated with “over-dipper” cases. Linear regression analyses were conducted to determine the correlation between various clinical variables and pCVD. Results In clinical characteristics, over-dippers exhibited lower pCVD values compared to non-dippers or dippers (P = 0.004). High diurnal intraocular pressure (IOP) fluctuation (P = 0.031), high diurnal mean arterial pressure (MAP) fluctuation (P = 0.001), and low pCVD (P = 0.002) were identified as predictors of being “over-dipper” in multivariable logistic regression analyses. Moreover, peripapillary retinal vessel density (P = 0.040), presence of choroidal microvasculature dropout (P = 0.039), and nocturnal MAP dip % (P = 0.002) showed significant correlations with pCVD according to multivariable linear regression analyses. Conclusion Over-dippers presented with lower pCVD than non-dippers or dippers as measured by OCTA choroidal images. Low pCVD was a predictor of “over-dipper” cases and associated with a greater percentage of nocturnal MAP dip in NTG patients. 24-h ambulatory BP monitoring may provide further information for detecting low pCVD in NTG patients with nocturnal BP dip.